A Non-Vacuum Coating Process That Fully Achieves Technical Goals of Bipolar Plates via Synergistic Control of Multiple Layer-by-Layer Strategy - Qiaoling Liu; Xiaole Chen; Menghan Wu; Weihao Wang; Yinru Lin; Zilong Chen; Shuhan Yang; Yuhui Zheng; Qianming Wang (Molecules, 2025)
The primary challenge associated with stainless steel in fuel cell operation is its susceptibility to corrosion, which leads to increased contact resistance and subsequent degradation of electrochemical performance. In general, the protective layers have been loaded onto the metal surface by widely used traditional techniques such as physical vapor deposition (PVD), or cathode arc ion plating. However, the above sputtering and evaporation ways require a high-vacuum condition, complicated experimental setups, higher costs, and an elevated temperature. Therefore, herein the achievement for uniform coatings over a large surface area has been realized by using a cost-effective strategy through a complete wet chemical process. The synergistic regulation of two conductive components and a plastic additive has been employed together with the entrapment of a surfactant to optimize the microstructure of the coating surface. The assembly of layered graphite and a polystyrene sphere could maintain both the high corrosion resistance feature and excellent electrical conductivity. In particular, the intrinsic vacant space in the above physical barriers has been filled with fine powders of indium tin oxide (ITO) due to its small size, and the interconnected conductive network with vertical/horizontal directions would be formed. All the key technical targets based on the U.S. Department of Energy (DOE) have been achieved under the simulated operating environments of a proton exchange membrane fuel cell. The corrosion current density has been measured as low as 0.52 μA/cm2 (for the sample of graphite/mixed layer) over the applied potentials from −0.6 V to 1.2 V and its protective efficiency is evaluated to be 99.8%. The interfacial contact resistance between the sample and the carbon paper is much less than 10 mΩ·cm2 (3.4 mΩ·cm2) under a contact pressure of 165 N/cm2. The wettability has been investigated and its contact angle has been evolved from 48° (uncoated sample) to even 110°, providing superior hydrophobicity to prevent water penetration. Such an innovative approach opens up new possibilities for improving the durability and reducing the costs of carbon-based coatings.